Analisis Sistem Pengendalian Internal Atas Prosedur Pengeluaran Kas: Studi pada Perusahaan Properti - Adelia, Ega; Ratnawati, Dyah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to assess the effectiveness of the internal control system in managing cash disbursement processes within a property company based in Surabaya, using the COSO 2013 framework as the primary reference. Data were collected through company document analysis, direct observation over a five-month period, and interviews, applying a descriptive qualitative approach. The analytical method follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing or verification. To ensure data validity, Member checking and source triangulation techniques were employed. The findings reveal that the implementation of COSO principles within the company has reached approximately 94.12%, indicating a high level of effectiveness. However, weaknesses remain in the control environment component, particularly due to the accounting function not being located within the area unit under study, but instead managed at the regional level. This situation hinders the optimal performance of the internal control structure. Therefore, it is recommended that the company revise its organizational structure and strengthen internal controls to improve the effectiveness of cash disbursement management.